Educational product: the materiality of an integrated curriculum symposium (Research, Society and Development, 2021)
Professional master's and doctoral programs are focused on the proposal of an educational product. This article aims to present the steps for planning, developing and evaluating an educational product in the area of integrated curriculum, applied at the Federal Institute of Triângulo Mineiro – Ituiutaba Campus. This work, which was the result of a master's research, was exploratory and involved field research, with bibliographical research and use of the focus group for data collection, whose results were analyzed qualitatively. Based on the concepts of interdisciplinarity, integrated curriculum and integral human training and supported by Kaplún's three thematic axes for the creation of educational materials, we developed a symposium, seeking to contribute to the discussion and continuing education of teachers, disseminating knowledge on the topic of the integrated curriculum for the entire school community. From the evaluation of the educational product, we understand that the symposium brought benefits to the academic community, which took part in moments of training, discussion and exchange of practical experiences about the integrated curriculum.